Answer:
x = -4
Step-by-step explanation:
–2x + 1 – (–7x + 3) = –4 + 3(x – 2)
-2x + 1 + 7x - 3 = -4 + 3x - 6
-2x + 7x - 3x = -4 - 6 - 1 + 3
2x = -8
x = -8/2
x = -4
Answer:
11 and 11
Step-by-step explanation:
brainliest^:)
3 months of homework, w t h have u been doinggg
Answer:
9/2
Step-by-step explanation:
2/3 + 3/4 + 5/6 + 4/8 + 3/12 + 3/2 =
= 16/24 + 18/24 + 20/24 + 12/24 + 6/24 + 36/24
= 108/24
= 54/12
= 9/2
Answer:
(1 cm)cos3πt
Step-by-step explanation:
Since the piston starts at its maximal height and returns to its maximal height three times evert 2 seconds, it is modelled by a cosine functions, since a cosine function starts at its maximum point. So, its height h = Acos2πft
where A = amplitude of the oscillation and f = frequency of oscillation and t = time of propagation of oscillation.
Now, since the piston rises in such a way that it returns to the maximal height three times every two seconds, its frequency, f = number of oscillations/time taken for oscillation where number of oscillations = 3 and time taken for oscillations = 2 s
So, f = 3/2 s =1.5 /s = 1.5 Hz
Also, since the the piston moves between 3 cm and 5 cm, the distance between its maximum displacement(crest) of 5 cm and minimum displacement(trough) of 3 cm is H = 5 cm - 3 cm = 2 cm. So its amplitude, A = H/2 = 2 cm/2 = 1 cm
h = Acos2πft
= (1 cm)cos2π(1.5Hz)t
= (1 cm)cos3πt